The Potentials of Robusta Coffee Seed Extract as Antioxidant on Kidney Histopathology in Mice Exposed to Monosodium Glutamate: Potensi Pemberian Ekstrak Biji Kopi Robusta sebagai Antioksidan Terhadap Gambaran Histopatologi Ginjal Mencit yang Dipapar Monosodium Glutamat - Wisudawati, Feby Dwi; Hidajati, Nove; Fikri, Faisal; Santoso, Kuncoro Puguh; Saputro, Amung Logam; Purnama, Muhammad Thohawi Elziyad (Veterinary Biomedical and Clinical Journal, 2023)
The purpose of this study was to determine the potential of administration robusta coffee extract as an antioxidant on the renal histopathology in mice exposed to monosodium glutamate (MSG) orally. This study used 20 adult male rats with Balb C strain divided into 5 experimental groups, namely K + (MSG 0.12 mg / head and Vitamin C 6 mg/mice), K- (MSG 0.12 mg/mice and Sodium carboxymethyl cellulose (CMC Na) 0,1 ml/mice), P1 (MSG 0.12 mg/mice and Robusta coffee extract 0.1 mg/mice), P2 (MSG 0.12 mg/mice and Robusta coffee extract 0.2 mg/mice), and P3 (MSG 0.12 mg/mice and 0.4 mg Robusta coffee extract mg/mice). The experimental group was treated every day at intervals between MSG and Vitamin C, CMC Na, and Robusta coffee extract for 60 min, the treatment was carried out for 42 days. Kidney histopathology scores were analyzed using the Saphiro-Wilk and Levene test to evaluate homogeneity, followed by the Kruskal Wallis test. The results of the Saphiro Wilk and Levene statistical analysis obtained p<0.05, thus the data continued with the Kruskal Wallis test scores of kidney cell damage obtained 0.043 which showed that the data were significant. The mean score of kidney cell damage in the treatment groups was K+ 1.60; K- 1.63; P1 1.70; P2 1.63; and P3 1.73. The conclusion is that Robusta coffee bean extract did not show a decrease in kidney cell damage that was different between treatment groups. Further research is needed to find out about the effect of different dosages of Robusta Coffee Extract to different organs